Manipulation of Legal Regulations in Commodification of Organ Transplants: Indonesia Perspective - Bakhtiar, Handar Subhandi; Maddussila, Samsu Alam (Universitas Negeri Semarang, 2024)
Organ transplantation serves as a critical solution for patients in need of organ donors. However, the pressing demand for organs, coupled with donors' economic hardships, has raised concerns about organ transplants being conducted for commercial purposes. This study aims to analyze the legal framework governing organ transplantation and explore the practices observed within society. Using secondary data comprising legislation, scholarly articles, scientific research, and online news reports, this study identifies significant inconsistencies and potential ambiguities within the regulatory framework. Current legal provisions stipulate that organ transplants must be conducted solely for humanitarian purposes and explicitly prohibit commercialization. Yet, government regulations create a loophole by allowing donors to receive awards, which could be exploited for commercial gains. To prevent the commercialization of organ transplants, it is essential to ensure that the relationship between donors and recipients is based on familial or kinship ties. Such relationships foster the principles of voluntariness and altruism, which are central to ethically sound transplantation practices. Strengthening the legal framework to eliminate ambiguities and promoting public awareness about ethical transplantation practices are imperative steps to uphold the integrity of organ donation and transplantation. This study underscores the importance of aligning regulatory frameworks with ethical principles to address the challenges posed by commercialization while ensuring equitable access to life-saving organ transplants.